Helicobacter pylori infection prevalence declined among an urban health check-up population in Chengdu, China: a longitudinal analysis of multiple cross-sectional studies - Zou, Jin-Chen; Wen, Mao-Yao; Huang, Yan; Chen, Xin-Zu; Hu, Jian-Kun; , on behalf of the SIGES Research Group (Frontiers in Public Health, 2023)
Objectives The efficacy of updated health policy in improving the generalization of Helicobacter pylori screening and eradication in southwest China was assessed in a longitudinal analysis of multiple cross-sectional studies from an institution. Methods In the periods 2009–2010, 2013–2014, and 2019–2021, 8,365, 16,914, and 18,281 urban observations from health check-ups at West China Hospital were analyzed, respectively. The 14C-urea or 13C-urea breath test was consistently used for H. pylori detection. The protocol has been reported elsewhere (PROSPERO Registration number: CRD42019120764). Results The overall prevalence of H. pylori dramatically decreased from 53.1% to 30.7% over the past decade (OR = 0.39, 95% CI 0.37–0.41), with a similar decline in all sex-specific and age-specific subgroups. The age-specific prevalence consistently increased before 40 years of age and always peaked at 50–59 years. Longitudinal clearance increased along with aging, and prevalence dropped to 22.6%, 25.1%, and 23.6% in the 40–49, 50–59, and 60–69 years initial age groups, respectively. Conclusion The generalization of H. pylori screening and eradication could greatly contribute to the control of H. pylori infection among urban health check-up populations and lower gastric cancer incidence.